Signs of State and Their Historical Modifications - Lyubashits, Valentin Ya.; Razuvaev, Nikolay V.; Mamychev, Alexey Yu.; Shestopal, Sergey S.; I., Benedyk V. (Journal of History Culture and Art Research, 2018)
This study considers various historical types of the state and implementation of their universal characteristics by implementing a comparative analysis. It is shown that the traditional state had a private-law basis; a basis of the states of modern type is the public law; in the traditional state the territory acted in the form of the earth belonging to the state on the right of the supreme property; in the modern state - as geographical space to which its power extends; supremacy of the traditional state was shown in the form of sovereignty, and the state of modern type - sovereignty; the power of the traditional state has property (personal), and the modern state - political (public) character. Historical types of the state differently realize its universal characteristics, getting the special signs which are historical modifications of these characteristics in the course of evolution.